Analisa Pengaruh Plugging Evaporator Terhadap Performance Desalination Plant Unit 2 PLTGU Gresik - Prayudi Prayudi; Retno Aita Diantari; Sofian Dwi Susilo (JURNAL POWERPLANT, 2015)
Analysis of Effect of Plugging Evaporator Against Performance Desalination Plant Unit 2 PLTGU Gresik is the analysis that discusses the effect of plugging tubes evaporator on the performance of Desaliantion Plant Unit 2 Type MSF-Once Through in PLTGU Gresik by calculating heat transfer in the evaporator and tubes Condenser, in which the calculation includes calculation before plugging the rate of heat transfer, heat transfer rate after plugging and loss of thermal efficiency at the desalination plant due to the effect of plugging the evaporator. After calculating heat transfer occurs, then analyze the results of the calculation of how much influence the evaporator tubes plugging of the desalination plant performance. Where the results are compared with the theoretical calculations of data - data that is in the specification Desaliantion Plant Unit 2 PLTGU Gresik type MSF-Once Through, whether appropriate or not then draw conclusions from such comparisons.